Endurance Diabetes Foot Exercise Based on Family Centered Care (EDFE-BFCC) to Reduce Blood Sugar Levels Patients Diabetes Mellitus Type 2 - Parellangi, Parellangi (Health Notions, 2022)
Patients diabetes mellitus type 2 have the potential to suffer from various complications, both acute and chronic complications. The family in addition to providing support also has an important role in the process of preventing these complications. So the purpose of this study was to determine the effectiveness of endurance diabetes foot exercise based on family centered care (SKDE-FCC) in reducing blood sugar levels patients diabetes mellitus type 2 in the work area of Bengkuring Public Health Center, Samarinda. This study used a quasi-experimental research design with a pre and post test research design without a control group. Diabetic foot exercise is modified with endurance movement, which is then through family empowerment to train family members with diabetes mellitus type 2. The effectiveness of the treatment was assessed by comparing the value of blood sugar levels during pre and post intervention. The results showed that p value = 0.001